2008
DOI: 10.1152/ajpcell.00544.2007
|View full text |Cite
|
Sign up to set email alerts
|

LPA modulates monocyte migration directly and via LPA-stimulated endothelial cells

Abstract: Gustin C, Van Steenbrugge M, Raes M. LPA modulates monocyte migration directly and via LPA-stimulated endothelial cells. Am J Physiol Cell Physiol 295: C905-C914, 2008. First published July 16, 2008 doi:10.1152/ajpcell.00544.2007.-Lysophosphatidic acid (LPA) is a bioactive lysophospholipid ligand present in oxidized low-density lipoprotein. The effects of LPA were investigated, first separately on endothelial cells (EC) and monocytes. Using Ki16425 (an LPA1 and LPA3 receptor antagonist), GW9662 [a peroxisome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 45 publications
(47 reference statements)
1
32
0
Order By: Relevance
“…Silencing EDI3 was previously shown to decrease levels of the signaling lipids, LPA and PA (6). As LPA is the direct metabolic product of GPAM, and several studies have described a role for LPA in migration (34)(35)(36), we compared the effect of EDI3, GPAM, and CHKA on intracellular LPA levels. Upon silencing, both EDI3 and GPAM, but not CHKA caused a comparable decrease in intracellular LPA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing EDI3 was previously shown to decrease levels of the signaling lipids, LPA and PA (6). As LPA is the direct metabolic product of GPAM, and several studies have described a role for LPA in migration (34)(35)(36), we compared the effect of EDI3, GPAM, and CHKA on intracellular LPA levels. Upon silencing, both EDI3 and GPAM, but not CHKA caused a comparable decrease in intracellular LPA levels.…”
Section: Discussionmentioning
confidence: 99%
“…The sn-1 alkyl analogs of LPA were shown to be more prevalent in the mildly oxidized LDL, and are 20 times more potent than the acyl analogs in platelet activation (257). In addition to promoting chemokine expression by endothelial cells, LPA stimulates the uptake of OxLDL itself through upregulation of scavenger receptor A in macrophages (41), and increases monocytes migration at low concentrations (83). It was also shown to stimulate SMC proliferation through the activation of the transcription factor Egr-1 (48).…”
Section: Oxldl In Atherosclerosis and Autoimmune Diseasesmentioning
confidence: 99%
“…Through a G i -dependent pathway, LPA up-regulated ROS production in mouse and human alveolar macrophages as well as Ca 2+ mobilization, IL-1β and TNFα transcription and protein expression in the mouse J774A.1 macrophage cell line and human monocyte-derived macrophages 81,202,204,214 . Cell migration was also controlled by LPA 1 and/or LPA 3 , as monocytic cells appeared to migrate toward concentrations of LPA < 1 μM, whereas migration is inhibited above this concentration in vitro 215 . The potential relevance of these receptors to the modulation of monocyte and macrophage recruitment during disease states is evident in models of atherosclerosis, where it was recently shown that macrophages in human atherosclerotic plaques expressed both of these receptors 216 .…”
Section: Immune Systemmentioning
confidence: 99%